Ketika Partai Memaksa, Kursi Menolak: Kontestasi Otoritas dalam Pergantian Ketua DPRD Provinsi Sulawesi Tenggara dari Partai NasDem (2025–2026) - La Ode Efrianto; Dasmin; Komang Jaka Ferdian (Indonesian Democracy Research Center, 2026)
This article examines the institutional resistance to the replacement of the Speaker of the Regional Legislative Council (DPRD) of Southeast Sulawesi Province, La Ode Tariala, who was formally dismissed by the NasDem Party Central Board through Decree No. 28A-SK/AKD/DPP-NasDem/XI/2025 in November 2025. The dismissal was not triggered by ethical or legal violations, but by the party's perception that Tariala was functionally too close to Governor Andi Sumangerukka, thereby weakening the legislature's supervisory role. Remarkably, despite the issuance of the party's decree, the interim replacement (PAW) process in the DPRD repeatedly failed to achieve a quorum through mid-2026—marking a form of institutional resistance not previously examined in Indonesian political science literature. Applying a qualitative case study approach within the theoretical frameworks of principal-agent theory and legislator dual-loyalty, this article argues that the conflict reflects a structural contradiction between party discipline logic and the logic of local legislative institutional autonomy. Findings reveal a gap between parties' formal authority over PAW mechanisms and legislators' factual capacity to delay replacement through internal procedure. This study contributes to ongoing debates about party dominance in Indonesia's post-reform parliament.